2007
DOI: 10.1029/2006jd007563
|View full text |Cite
|
Sign up to set email alerts
|

Forest fire plumes over the North Atlantic: p‐TOMCAT model simulations with aircraft and satellite measurements from the ITOP/ICARTT campaign

Abstract: [1] Intercontinental Transport of Ozone and Precursors (ITOP) (part of International Consortium for Atmospheric Research on Transport and Transformation (ICARTT)) was an intense research effort to measure long-range transport of pollution across the North Atlantic and its impact on O 3 production. During the aircraft campaign plumes were encountered containing large concentrations of CO plus other tracers and aerosols from forest fires in Alaska and Canada. A chemical transport model, p-TOMCAT, and new biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 52 publications
1
73
0
Order By: Relevance
“…Photochemical impact remains uncertain. Clearly, long-range-transported biomass burning plumes can influence Europe (Cook et al, 2007;Real et al, 2007), though the impact is variable (Hudman et al, 2004). More recently, European fires in Portugal and Russia have been shown to contribute to air pollution (Tressol et al, 2008;Martins et al, 2012), and the frequency is expected to increase with climate change (Carvalho et al, 2011).…”
Section: Biomass Burningmentioning
confidence: 99%
“…Photochemical impact remains uncertain. Clearly, long-range-transported biomass burning plumes can influence Europe (Cook et al, 2007;Real et al, 2007), though the impact is variable (Hudman et al, 2004). More recently, European fires in Portugal and Russia have been shown to contribute to air pollution (Tressol et al, 2008;Martins et al, 2012), and the frequency is expected to increase with climate change (Carvalho et al, 2011).…”
Section: Biomass Burningmentioning
confidence: 99%
“…Model studies have also found that limiting fire emissions to the boundary layer underestimates their influence in downwind regions (Cook et al, 2007;Freitas et al, 2007;Brioude et al, 2009;Chen et al, 2009;Jian and Fu, 2014). More effort is needed to evaluate model simulation of ozone production from biomass burning emissions, in particular during the evolution of fire plumes and over regions that are dominated by biomass burning emissions (e.g., Mauzerall et al, 1998;Alvardo et al, 2010;Singh et al, 2010;Arnold et al, 2015).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…It has been used extensively for tropospheric studies and is described in more detail in Cook et al (2007) and Hamilton et al (2008). For this study, the model was run at a relatively high horizontal resolution (1 • ×1…”
Section: Model Descriptionmentioning
confidence: 99%
“…Several HO x (OH and HO 2 ) regeneration mechanisms have been proposed to resolve these differences (e.g. Lelieveld et al, 2008;Peeters et al, 2009;Da Silva et al, 2010;Paulot et al, 2009). Inclusion of these mechanisms in model chemistry schemes has the potential to influence our understanding of the extent to which changes in isoprene emissions could affect oxidising capacity (Archibald et al, 2010b).…”
mentioning
confidence: 99%